MEMFASILITASI HIGHER ORDER TIHINKING SKILLS DALAM PERKULIAHAN BIOLOGI SEL MELALUI MODEL INTEGRASI ATRIBUT ASESMEN FORMATIF - Sigit Saptono; Nuryani Y Rustaman; Saefudin Saefudin; Ari Widodo (Universitas Sultan Ageng Tirtayasa, 2016)
ABSTRACTHigher order thinking skills are needed to understand the problem and the essence of the lecture material Biology Sel. Study design Research and Development aims to develop reasoning skills and analytic thinking biology student teachers through the application of learning models Integration Attributes Formative Assessment (IAAF). Some 61 students of Biology Education Semarang State University who is doing his third semester courses Cell Biology is the subject of research. Analytical reasoning and thinking ability of students is measured through individual assignments, group assignments concept map creation and preparation of the Review articles, and 30 items about the shape of the selected response and constructed response questions, validated questions. The result showed that the ability of reasoning and analytical thinking of students can be expanded significantly, although the development of the ability of argumentation, one category of analytic thinking skills, they need serious attention.